On the stable range of matrix rings - Zabavskii, B. V.; Petrichkovich, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
It is shown that an adequate ring with nonzero Jacobson radical has a stable range 1. A class of matrices over an adequate ring with stable range 1 is indicated.